2014
DOI: 10.1371/journal.pone.0087373
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin and Rab5 Complex Is Requited for Uptake of Staphyrococcus aureus and Interleukin-6 Expression

Abstract: Vinculin, a 116-kDa membrane cytoskeletal protein, is an important molecule for cell adhesion; however, little is known about its other cellular functions. Here, we demonstrated that vinculin binds to Rab5 and is required for Staphylococcus aureus (S. aureus) uptake in cells. Viunculin directly bound to Rab5 and enhanced the activation of S. aureus uptake. Over-expression of active vinculin mutants enhanced S. aureus uptake, whereas over-expression of an inactive vinculin mutant decreased S. aureus uptake. Vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 94 publications
1
18
0
Order By: Relevance
“…Rab5 is a GTPase that regulates endocytosis, previously shown to associate vinculin (Hagiwara et al, 2014;Mendoza et al, 2013); Rab5-positive vesicles also act as platforms for Rac1 trafficking to promote CDR formation (Lanzetti et al, 2004;Palamidessi et al, 2008). Since our results demonstrate that LIPUS promotes the formation of both endosomes and CDRs, we hypothesized that Rac1 activation after LIPUS stimulation may require Rab5.…”
Section: Rac1 Activation Requires Functional Rab5mentioning
confidence: 61%
See 1 more Smart Citation
“…Rab5 is a GTPase that regulates endocytosis, previously shown to associate vinculin (Hagiwara et al, 2014;Mendoza et al, 2013); Rab5-positive vesicles also act as platforms for Rac1 trafficking to promote CDR formation (Lanzetti et al, 2004;Palamidessi et al, 2008). Since our results demonstrate that LIPUS promotes the formation of both endosomes and CDRs, we hypothesized that Rac1 activation after LIPUS stimulation may require Rab5.…”
Section: Rac1 Activation Requires Functional Rab5mentioning
confidence: 61%
“…The same study demonstrated that cell migration promotes the formation of a complex of Rab5 with β1 integrin, FAK, paxillin and vinculin, and that FAs are enriched with GTP-bound Rab5 (Mendoza et al, 2013). Furthermore, associations between β1 integrin and Rab5 (Pellinen et al, 2006), and vinculin and Rab5 (Hagiwara et al, 2014), have been observed, pertinent to our findings that Rac1 activation requires both vinculin and Rab5, and that vinculin appears to regulate the behaviour and morphology of Rab5-positive vesicles ( Fig. 7G,H; Movie 4).…”
Section: The Link Between Adhesion Proteins and Rab5mentioning
confidence: 83%
“…VNC is able to affect the expression of interleukin 6 whose upregulation might be determinant for the upregulation of Fibrinogen gamma chain, alpha‐2‐macroglobulin, complement C3, and miR 342–3p …”
Section: Resultsmentioning
confidence: 99%
“…Amoebic Rab5, like its human homologue, participates in the early phase of transferrin endocytosis (Fig. A and D) (Bucci et al ., ; Schnatwinkel et al ., ; Leclerc et al ., ; Hagiwara et al ., ). In contrast, Rab7A, the closest Rab7 isotype to its human homologue, showed significant deviation in terms of localization and role in intracellular trafficking.…”
Section: Discussionmentioning
confidence: 97%